Ketoprofen Lysine Salt Versus Corticosteroids in Early Outpatient Management of Mild and Moderate COVID-19: A Retrospective Study - Domenica Francesca Mariniello; Raffaella Pagliaro; Vito D’Agnano; Angela Schiattarella; Fabio Perrotta; Andrea Bianco (Pharmacy)
Background: Accelerating recovery and preventing the progression to more severe outcomes for patients with coronavirus disease 2019 (COVID-19) is of paramount importance. Non-steroidal anti-inflammatory agents (NSAIDs) have been widely adopted in the international recommendations for non-severe COVID-19 management. Among NSAIDs, evidence about the efficacy of ketoprofen lysin salt (KLS) in the treatment of non-severe COVID-19 has not been reported. Methods: This retrospective study compared the outcomes of 120 patients with mild to moderate COVID-19 treated at home with KLS between March 2021 and May 2023 compared with the outcomes of 165 patients who received corticosteroids. The outcomes included hospitalization, the need for oxygen supplementation, clinical recovery from acute COVID-19, and time to negative swabs. Results: Symptoms persisted in a lower percentage of patients in the KLS group compared to the corticosteroids group (p < 0.0001) and for a shorter period (p = 0.046). We found 6 patients (5%) in the KLS group were hospitalized compared to 45 (27%) in the corticosteroids group (p < 0.001). A higher percentage of patients in the corticosteroids group require oxygen administration (p < 0.001). In addition, patients taking corticosteroids showed a longer viral shedding period compared to those taking KLS (p = 0.004). A final multivariate analysis suggests that KLS might reduce hospitalization risk, the need for oxygen supplementation, and the persistence of post-COVID-19 symptoms when compared to an oral corticosteroid after adjusting for significant co-variables. Conclusions: KLS might have a positive effect on clinical recovery in non-severe COVID-19 patients. A comparison with other NSAIDs in terms of difference in efficacy and safety should be investigated in further trials.